Seismic constraints on the architecture of the Newport‐Inglewood/Rose Canyon fault: Implications for the length and magnitude of future earthquake ruptures. Issue 3 (11th March 2017) - Sahakian, Valerie; Bormann, Jayne; Driscoll, Neal; Harding, Alistair; Kent, Graham; Wesnousky, Steve
Abstract: The Newport‐Inglewood/Rose Canyon (NIRC) fault zone is an active strike‐slip fault system within the Pacific‐North American plate boundary in Southern California, located in close proximity to populated regions of San Diego, Orange, and Los Angeles counties. Prior to this study, the NIRC fault zone's continuity and geometry were not well constrained. Nested marine seismic reflection data with different vertical resolutions are employed to characterize the offshore fault architecture. Four main fault strands are identified offshore, separated by three main stepovers along strike, all of which are 2 km or less in width. Empirical studies of historical ruptures worldwide show that earthquakes have ruptured through stepovers with this offset. Models of Coulomb stress change along the fault zone are presented to examine the potential extent of future earthquake ruptures on the fault zone, which appear to be dependent on the location of rupture initiation and fault geometry at the stepovers. These modeling results show that the southernmost stepover between the La Jolla and Torrey Pines fault strands may act as an inhibitor to throughgoing rupture due to the stepover width and change in fault geometry across the stepover; however, these results still suggest that rupture along the entire fault zone is possible. Key Points: The Newport‐Inglewood/Rose Canyon fault zone appears to be one, continuous fault zone, with small stepovers This study finds four main strands and three main stepovers in the NIRC fault zone Ruptures on this fault could produce up to M 7.4 earthquake